A Roadmap Toward Building Trust in AI Environment: Research Agenda - Kwon, Ik-Whan G.; Kim, Sung-Ho (British Journal of Healthcare and Medical Research, 2025)
This paper explores the critical interplay between trust in AI technology and trust in its deployment, focusing on the gaps in interpersonal trust often overlooked in AI adoption. While AI enhances operational efficiency and decision-making, it struggles to replicate the emotional and psychological foundations of human trust. Drawing on interdisciplinary literature, the study highlights three trust dimensions—technological, organizational, and user-centric—and their misalignment, which fuels skepticism about AI reliability and ethical behavior. Despite AI's potential to transform industries, trust deficits persist due to concerns about transparency, accountability, and the emotional resonance of AI. The findings underscore that trust in AI must evolve as a complementary construct, bridging human and machine interactions without displacing interpersonal trust. The study proposes a framework emphasizing cultural and organizational adaptation, regulatory oversight, and user engagement to foster a balanced, sustainable AI.